2007
DOI: 10.1007/s11661-007-9095-8
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibria and Phase Transition of the Ni–Fe–Ga Ferromagnetic Shape Memory Alloy System

Abstract: KATSUNARI OIKAWA, TOSHIHIRO OMORI, YUJI SUTOU, HARUHIKO MORITO, RYOSUKE KAINUMA, and KIYOHITO ISHIDA Phase equilibria and martensitic and magnetic transitions of the b (B2 and L2 1 ) phase in the Ni-Fe-Ga system were investigated. The b phase was found to be in equilibrium with the g (A1 structure) or g9 (L1 2 structure) phase. The Curie temperature, T C , equilibrium temperature, T 0 5 (M s 1 A f )/2, martensitic transition starting temperature, M s , and reverse transition finishing temperature, A f , of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 41 publications
4
36
0
1
Order By: Relevance
“…This behavior agrees with the phenomenological model based on a Bragg-Williams approximation recently proposed to describe the evolution of the magnetic contribution to the total entropy change in Ni-Mn-based alloys [34] (a similar behavior has been also reported in Ni-Fe-Ga ferromagnetic shape memory alloys [35]). The absence of a marked change in the slope (previously reported) seems to be due to the paramagnetic nature of martensite in the present Ni-Mn-In-Co alloy.…”
Section: Resultssupporting
confidence: 90%
“…This behavior agrees with the phenomenological model based on a Bragg-Williams approximation recently proposed to describe the evolution of the magnetic contribution to the total entropy change in Ni-Mn-based alloys [34] (a similar behavior has been also reported in Ni-Fe-Ga ferromagnetic shape memory alloys [35]). The absence of a marked change in the slope (previously reported) seems to be due to the paramagnetic nature of martensite in the present Ni-Mn-In-Co alloy.…”
Section: Resultssupporting
confidence: 90%
“…Although the rapidly solidified ribbons are reported to show higher T M than annealed ribbons, it can be seen that T 0 has almost linear dependence to the e/a with nearly the same slope for each Al content. This feature is very similar to the above FSMAs [14]. Oikawa et al also showed that the saturation magnetization value, measured at low temperature T ¼ 83 K and at high magnetic field 7 T, had linear dependence with the magnetic valence Z m .…”
Section: Discussionsupporting
confidence: 84%
“…All of the above FSMAs obey almost the same Z m dependence. The Curie temperature T C also has linear dependence with the Z m [14]. Fig.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations